Both combinatorial K4me0-K36me3 marks on sister histone H3s of a nucleosome are required for Dnmt3a-Dnmt3L mediated de novo DNA methylation. (20th February 2020) - Gong, Ting; Gu, Xin; Liu, Yu-Ting; Zhou, Zhen; Zhang, Ling-Li; Wen, Yang; Zhong, Wei-Li; Xu, Guo-Liang; Zhou, Jin-Qiu
Abstract: A nucleosome contains two copies of each histone H2A, H2B, H3 and H4. Histone H3 K4me0 and K36me3 are two key chromatin marks for de novo DNA methylation catalyzed by DNA methyltransferases in mammals. However, it remains unclear whether K4me0 and K36me3 marks on both sister histone H3s regulate de novo DNA methylation independently or cooperatively. Here, taking advantage of the bivalent histone H3 system in yeast, we examined the contributions of K4 and K36 on sister histone H3s to genomic DNA methylation catalyzed by ectopically co-expressed murine Dnmt3a and Dnmt3L. The results show that lack of both K4me0 and K36me3 on one sister H3 tail, or lack of K4me0 and K36me3 on respective sister H3s results in a dramatic reduction of 5mC, revealing a synergy of two sister H3s in DNA methylation regulation. Accordingly, the Dnmt3a or Dnmt3L mutation that disrupts the interaction of Dnmt3a ADD domain-H3K4me0, Dnmt3L ADD domain-H3K4me0, or Dnmt3a PWWP domain-H3K36me3 causes a significant reduction of DNA methylation. These results support the model that each heterodimeric Dnmt3a-Dnmt3L reads both K4me0 and K36me3 marks on one tail of sister H3s, and the dimer of heterodimeric Dnmt3a-Dnmt3L recognizes two tails of sister histone H3s to efficiently execute de novo DNA methylation.